2017
DOI: 10.1097/ogx.0000000000000416
|View full text |Cite
|
Sign up to set email alerts
|

Selfish Drive Can Trump Function When Animal Mitochondrial Genomes Compete

Abstract: Mitochondrial genomes compete for transmission from mother to progeny. We explored this competition by introducing a second genome into Drosophila melanogaster to follow transmission.Competitions between closely related genomes favored those functional in electron transport, resulting in a host-beneficial purifying selection 1 . Contrastingly, matchups between distant genomes often favored those with negligible, negative or lethal consequences, indicating selfish selection. Exhibiting powerful selfish selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Here we show that the segregation of mtDNA heteroplasmy likely plays a role in shaping D-loop population polymorphisms by a mechanism operating within the female germline. Similar findings have been seen in Drosophila where D-loop variants 'selfishly' drive segregation favoring a specific mtDNA genotype(32). These observations have implications for the development of mitochondrial transfer techniques for preventing the inheritance of severe pathogenic mtDNA mutations in humans(33,34).…”
supporting
confidence: 65%
“…Here we show that the segregation of mtDNA heteroplasmy likely plays a role in shaping D-loop population polymorphisms by a mechanism operating within the female germline. Similar findings have been seen in Drosophila where D-loop variants 'selfishly' drive segregation favoring a specific mtDNA genotype(32). These observations have implications for the development of mitochondrial transfer techniques for preventing the inheritance of severe pathogenic mtDNA mutations in humans(33,34).…”
supporting
confidence: 65%
“…Studies in several systems suggested that purifying selection in the female germline reduces transmission of detrimental mitochondrial mutations [1][2][3][4][5][6][7]. In contrast, some selfish genomes can take over despite a cost to host fitness [8][9][10][11][12][13]. Within individuals, the outcome of competition is therefore influenced by multiple selective forces.…”
mentioning
confidence: 99%
“…The potential risks from "selfish" mtDNAs [35] might be reduced by haplotype matching, that is, using donors who harbour mtDNA that is closely related to the recipient. However, such a regime would be difficult to implement.…”
Section: Mitochondrial Replacement Therapy: Practical Issues and Mtdnmentioning
confidence: 99%